Neutrosophic Bipolar Vague Set and its Application to Neutrosophic Bipolar Vague Graphs - S. Satham Hussain; R. Jahir Hussain; Young Bae Jun; Smarandache, Florentin (Neutrosophic Sets and Systems, 2019)
A bipolar model is a significant model wherein positive data revels the liked object, whilenegative data speaks the disliked object. The principle reason for analysing the vague graphs is todemonstrate the stability of few properties in a graph, characterized or to be characterized in usingvagueness. In this present research article, the new concept of neutrosophic bipolar vague sets areinitiated. Further, its application to neutrosophic bipolar vague graphs are introduced. Moreover,some remarkable properties of strong neutrosophic bipolar vague graphs, complete neutrosophicbipolar vague graphs and complement neutrosophic bipolar vague graphs are explored and theproposed ideas are outlined with an appropriate example.